-13
4
16
24
None of the above
-8
-6
8
6
9
-9
-3
3
6
9
X = 10x = -6
X = 6
X = 4
X = -6
None of the above
Substituting values in for k
Subtracting 5k from both sides of the equation
Subtracting 2k from 2k and 5k.
Adding 2k to 5k
Dividing both sides of the equation by 2
Subtracting 3m from both sides of the equation
Combining 2m with 3m
Distributing the 2 into (m - 3)
Subtracting 3 from both sides of the equation
Substituting values into m
2x^5
2x^6
4x^5
4x^6
None of the above
10*sqrt(2)
2*sqrt(10)
5*sqrt(8)
100*sqrt(2)
None of the above